THE TREATMENT OF DEPRECIATION IN THE INTERSTATE COMMERCE COMMISSION VALUATION CASES. - Mason, Perry (The Accounting Review, 1928)
Abstract The U.S. Interstate Commerce Commission was specifically instructed to consider depreciation in making the valuation of the railroads of the country since cost of reproduction less depreciation was one of the three basic values to be determined and considered in setting final values upon the railroad properties. A study of the published valuation reports indicates that a very definite and comprehensive policy has been adopted which has been applied strictly and rigidly to all cases in spite of vigorous protests of the carriers. In the first published valuation case the commission stated that depreciation has been treated as covering number of units of capacity for service as compared with those existing in the same elements when Installed; and upon ascertaining what part of the remaining capacity for service remains, depreciation which has already accrued ii subtracted from the cost of reproduction new and the remainder given as cost of reproduction less depreciation, due consideration being given to existing salvage or scrap value. Depreciation is not taken merely as the equivalent of deferred maintenance or loss of service efficiency.